Peningkatan Kemampuan Menulis Puisi Kelas X SMK Negeri 2 Botomuzoi dengan Menggunakan Model Pembelajaran Discovery - Erwin Serius Lase; Riana (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to improve students' ability to write poetry by using the discovery learning model. The subjects of this study were 22 students of class X ATPH at SMK Negeri 2 Botomuzoi even semester. This study uses the Classroom Action Research model with the implementation procedures namely Planning, Action, Observation, Reflection. Based on the results of the study, there was an increase in students' abilities, seen in the assessment of the first cycle, the lowest score was 60 and the highest was 80 with an average value of 67.95. While the second cycle obtained the lowest value of 75 and the highest 95 with an average value of 84.77. The results of the first cycle of researchers at the first meeting were 57.14% and the second meeting was 64.28%. While cycle II the first meeting was 71.42% and the second meeting was 100%. While the results of observations of researchers in the first cycle of the first meeting were 46.75% and the second meeting were 48.05%. It can be concluded that the discovery learning model can improve the ability of class X students at SMK Negeri 2 Botomuzoi